Studi Pengaruh Suhu Permukaan Laut Di Selat Makassar Terhadap Intensitas Curah Hujan Kota Balikpapan - Kusmardiyanti, Retni; Yusuf, Mustaid; Djayus, Djayus; Rahmiati, Rahmiati (GEOSAINS KUTAI BASIN, 2022)
Rainfall is the amount of water that falls on the ground surface during a certain period measured in units of height and is caused by various factors, such as sea surface temperature, wind direction and speed, humidity and so on. This study aims to determine how the influence of the sea surface temperature of the Makassar Strait on the intensity of rainfall in the city of Balikpapan. The data used in this study are sea surface temperatures taken at 4 coordinate points in the Makassar Strait, they are -2oS and 118oE, -1oS and 118.25oE, ​​0oEQ and 118.5oE, ​​1oN and 119.25oE and 2oN and 119.5oE and rainfall data in Balikpapan City. taken at 4 points of data collection stations, they are -1.16oS and 116.84oE, -1.16oS and 116.88oE, -1.2oS and 116.84oE and -1.2oS and 116.88oE. The data was taken for 3 years, from 2017 to 2019. This study uses a correlation analysis, where the results obtained indicate that the sea surface temperature in the Makassar Strait quite affects rainfall in the city of Balikpapan. The highest correlation is 0.601217435, which is a strong correlation and has a positive value. Keywords : Rainfall, Sea Surface Temperature, Correlation Analysis